2011
DOI: 10.1007/s10495-011-0686-x
|View full text |Cite
|
Sign up to set email alerts
|

Preferential involvement of mitochondria in Toll-like receptor 3 agonist-induced neuroblastoma cell apoptosis, but not in inhibition of cell growth

Abstract: Double-stranded RNA (dsRNA) can mediate its therapeutic effect through Toll-like receptor 3 (TLR3) expressed on tumor cells including neuroblastoma. We used synthetic dsRNA polyinosinic-polycytidylic acid [Poly(I:C)] as a TLR3 agonist to treat TLR3-expressing SK-N-AS neuroblatoma (NB) cells. We found up-regulation of endoplasmic reticulum (ER) stress proteins glucose-regulated protein 78 and inositol-requiring enzyme 1. Bafilomycin A1, an inhibitor of ER function, effectively blocked poly(I:C)-induced activati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
21
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 38 publications
3
21
0
Order By: Relevance
“…Transcription of MnSOD is regulated by NF-κB, and involved in TLR3-mediated NB cell death. 26,35 A significantly increased MnSOD expression was found in poly (I:C)-treated AS xenografts (Po0.001, Figures 4c and d). Furthermore, ROS was visualized by 8-hydroxy-2'-deoxyguanosine (8-OHdG), revealing a stronger immunostaining of 8-OHdG in nuclei of tumor cells in poly(I:C)-treated xenografts than in controls (Po0.001, Figures 4c and e).…”
Section: Poly(i:c) Significantly Increased Nuclear Factor Kappab Actimentioning
confidence: 89%
See 4 more Smart Citations
“…Transcription of MnSOD is regulated by NF-κB, and involved in TLR3-mediated NB cell death. 26,35 A significantly increased MnSOD expression was found in poly (I:C)-treated AS xenografts (Po0.001, Figures 4c and d). Furthermore, ROS was visualized by 8-hydroxy-2'-deoxyguanosine (8-OHdG), revealing a stronger immunostaining of 8-OHdG in nuclei of tumor cells in poly(I:C)-treated xenografts than in controls (Po0.001, Figures 4c and e).…”
Section: Poly(i:c) Significantly Increased Nuclear Factor Kappab Actimentioning
confidence: 89%
“…32 Our previous studies have revealed that the levels of c-Myc are associated with TLR3 expression in NB patients and TLR3-induced signaling in NB cells. 21,26,27 However, the role of c-Myc in the innate immune system is still unknown. To uncover whether c-Myc expression is influenced by TLR3-mediated innate immunity, we first compared c-Myc and TLR3 expressions by IHC between the control and poly(I:C) treatment groups of AS xenografts.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations